A Study on the Mineral Dressing Test of Bauxite Ore in Central Guizhou Province, China - Wu, Yang (Journal of Mines, Metals and Fuels, 2022)
Guizhou province is one of the major bases of bauxite resource in China; but some of them had a low grade. In this study, couple of tests for the bauxite desliming were carried out to gain the best conditions and controlling parameter. The industrial water in Guizhou province has moderate hard water and so sodium hexametaphosphate not only can eliminate the influence of calcium and magnesium ions, but also acted as dispersant. Sodium silicate had similar disperse effects to sodium hexametaphosphate, and their dosage was similar too. In continuous operation, the hydraulic desliming equipment worked normally and reliably. When treating low grade bauxite with an Al-Si ratio of 4.71, bauxite concentrate with an Al-Si ratio of 6.78 and Al2O3 recovery of 85.14% can be obtained by the equipment.